2021
DOI: 10.1186/s12903-021-01427-0
|View full text |Cite
|
Sign up to set email alerts
|

FESEM evaluation of smear layer removal from conservatively shaped canals: laser activated irrigation (PIPS and SWEEPS) compared to sonic and passive ultrasonic activation—an ex vivo study

Abstract: Background Irrigation of the pulp space is a mandatory step to get rid of all its organic and inorganic content. Activation of the irrigants play a key role in the era of minimally invasive endodontics. The aim of this study was to assess the effectiveness of different irrigants activation methods in removing the smear layer at 1, 3, 5 and 8 mm from the apex from conservatively shaped canals. Methods Eighty-five human mandibular premolars were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…As a further development of the laser-based systems, SWEEPS showed even better results in hard tissue debris removal compared to PIPS [32]. Furthermore, SWEEPS seemed to be advantageous over sonic activation with EndoActivator in terms of smear layer removal [72].…”
Section: Discussionmentioning
confidence: 96%
“…As a further development of the laser-based systems, SWEEPS showed even better results in hard tissue debris removal compared to PIPS [32]. Furthermore, SWEEPS seemed to be advantageous over sonic activation with EndoActivator in terms of smear layer removal [72].…”
Section: Discussionmentioning
confidence: 96%
“…These results are consistent with those of previous studies where no significant differences were observed between the removal of the smear layer and debris in the apical and medium thirds of the root canal after manual-dynamic irrigation and sonic activation [ 32 , 53 ]. However, it was also reported in the literature that smear layer removal using PUI was significantly superior to manual irrigation [ 32 ] and that laser-activated irrigation was superior to sonic and ultrasonic irrigation techniques [ 54 ]. Better cleaning of root canal walls was also observed for laser-activated irrigation in comparison with standard needle irrigation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such requirement was replaced by the photoacoustic shockwaves induced with the pulsed laser within the irrigant travelling throughout the root canal framework, allowing its 3-D movement without the requirement for intracanal tip insertion. 26,[32][33][34][35][36][37] PIPS is a laser agitation technique, which employs the Er: YAG laser at 2940 nm. This technology relies on the high wavelength absorption of the Er: YAG laser in the pulp chamber filled with water-based irritants.…”
Section: Discussionmentioning
confidence: 99%
“…Apical sealing was highly improved on utilizing lasers for irrigant activation before obturation. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Further studies should be carried out to improve the effects of lasers and its combination with different irrigating solutions in eliminating the smear layer from the root canal walls. Further research on the diode laser for the practical use in endodontics is needed before it is clinically applied.…”
Section: Discussionmentioning
confidence: 99%